صليل السيوف في سيفيات المتنبي وأبي فراس: دراسة في جماليات البديع الإيقاعي - الحارثي، مازن بن محمد مريسي Alharethi, Mazen Bin Mohammed Marisi (جامعة قناة السويس - كلية الآداب والعلوم الإنسانية, 2023)
يقوم هذا البحث على تناول البديع الإيقاعي في قصيدتين من سيفيات المتنبي وأبي فراس الحمداني تناولاً جمالياً يهدف إلى الكشف عن جماليات الإيقاع ودوره في سبك النص، وإنتاج الدلالة. وذلك في إطار المنهج الوصفي السينكروني الذي يثبت الظاهرة المدروسة والفترة الزمنية. وقد تناول البحث من فنون البديع الإيقاعي في القصيدتين رد أعجاز الكلام على ما تقدمها، الجناس، الترديد، التعطف، الانسجام الإيقاعي وهي فنون تنضوي تحت النسق التكراري من نسقي البديع، والترصيع والتوازي التركيبي وهما من الفنون التي تنضوي تحت النسق المتوازي من نسقي البديع الإيقاعي العربي. وقد كشف البحث عن كثير من النتائج التي تبرهن على أصالة العقلية العربية في فهم موسيقية فن الشعر ومعاصرتها، وسبقها إلى الكثير من الفنيات التي تناولها النقد الغربي. كما كشف عن دور البديع الإيقاعي في التخييل الشعري، وتحقيق التكثيف في اللغة الشعرية والإيحائية، وتمدد المعنى وإنتاج الدلالة من خلال جدلية العلاقة بين المضمون الفكري وآليات النص. This research is based on dealing with the rhythmic beauty in two poems from Saifiat Al-Mutanabi and Abi Firas Al-Hamdani, an aesthetic approach aimed at revealing the aesthetics of rhythm and its role in molding the text and producing significance. This is within the framework of the synchronic descriptive approach, which establishes the studied phenomenon and the time period. The research dealt with the rhythmic arts of the beautiful in the two poems, the response of the miracles of speech to what they presented, anaphora, repetition, sympathy, rhythmic harmony, which are arts that fall under the repetitive pattern of the rhythmic patterns of the beautiful, and the inlay and synthetic parallelism, which are among the arts that fall under the parallel pattern of the rhythmic rhythmic patterns. The research revealed many results that prove the originality of the Arab mentality in understanding the music of the art of poetry and its contemporaneity, and preceded it to many of the techniques dealt with by Western criticism. It also revealed the role of the rhythmic masterpiece in poetic imagination, the achievement of intensification in poetic and suggestive language, the expansion of meaning and the production of significance through the dialectical relationship between the intellectual content and the mechanisms of the text.
Keywords: المتنبي، احمد بن الحسين، ت. 354 هـ. -- الحمداني، الحارث بن سعيد بن حمدان، ت. 357 هـ. -- الأدب العربي -- الشعر العربي -- البديع الإيقاعي